Manajemen Sarana Prasarana Pendidikan untuk Peningkatan Mutu Pendidikan di MTs Ma’arif NU 1 Patikraja - Muslikhudin Muslikhudin; Muh. Hanif (Transformasi Manageria: Journal of Islamic Education Management, 2024)
This research aims to evaluate the management of facilities and infrastructure and its influence on the quality of education. Using qualitative methods, the author directly observes schools, collects data, and analyzes information. The school's infrastructure is running well and supports student achievement, especially through self-development programs that help students express their talents and potential. PRasarana is a component that aims to support the teaching and learning process of students, facilities are more about the tools needed by students and the school, while infrastructure is more about the environment, a sense of comfort, security and order. Of course, if the facilities and infrastructure can be implemented well in the school environment, it will be a special attraction for students and prospective students. For example, this infrastructure includes yards, buildings, road access at schools and so on, these are usually what attract students when they are in that environment. The teacher's role in managing educational facilities and infrastructure begins with the planning, utilization and monitoring stages of the infrastructure.